Burya A.I., Yeriomina Ye.A., Reva A.G. Investigation of the influence of operating modes on the tribotechnical characteristics of carbon fiber reinforced plastic - Буря, А. И.; Ерёмина, Е. А.; Рева, А. Г. (Problems of Tribology, 2018)
The effect of operating modes on the tribotechnical characteristics of carbon fiber reinforced plastic by the method of mathematical experiment planning has been studied. The factors that have the greatest influence on the optimization parameter are determined. Extreme regimes of exploitation of carbon fiber reinforced plastic (with modified Mg nanoparticles) based on heat-resistant aromatic polyamide phenylone and mathematical models adequately describing the operation of the tribo-node are found.